PENERAPAN AKUNTANSI MURABAHAH BERDASARKAN PSAK NO.102 STUDI PADA KOPERASI SYARIAH KOTA BENGKULU - Faisal Muttaqin; Herry Novrianda; Selamet Fuadi (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2022)
The purpose of this study was to determine 1) the application of PSAK.102 on Murabahah transactions at the Syariah Consumer Cooperative Bengkulu 2) to determine the suitability of the Murabahah accounting treatment at the Al-Muawanah Syariah Consumer Cooperative UIN Fatmawati Sukarno Bengkulu based on PSAK No.102 . To test this, the researcher used a qualitative descriptive method with primary data collection techniques in the form of interviews with five informants. Data analysis techniques used are data reduction, data presentation and conclusions. From the results of the research and discussion it was found that 1) the Al-Muawanah Syariah Consumer Cooperative UIN Fatmawati Sukarno Bengkulu had implemented PSAK No. 102 and 2) the disclosure and recording of transactions was in accordance with the provisions of PSAK No. 102 regarding murabahah.